Campus emergency preparedness meeting ICS and NIMS compliance - Connolly, Maureen (Boca Raton, FL CRC Press, 2016)
"The book aids you in creating emergency response plans that comply with standards set by the ICS and NIMS. Ultimately, these are all-hazards strategies that can be applied to all phases of campus emergency management with efficient coordination among all levels of campus administration."--Provided by publisher.
Keywords: School crisis management -- United States